T-cell receptor therapy targeting mutant capicua transcriptional repressor in experimental gliomas - Kilian, Michael; Friedrich, Mirco; Sanghvi, Khwab; Green, Edward; Pusch, Stefan; Kawauchi, Daisuke; Löwer, Martin; Sonner, Jana K.; Krämer, Christopher; Zaman, Julia; Jung, Stefanie; Breckwoldt, Michael O.; et al. (Clinical cancer research, 2022)
Gliomas are intrinsic brain tumors with a high degree of constitutive and acquired resistance to standard therapeutic modalities such as radiotherapy and alkylating chemotherapy. Glioma subtypes are recognized by characteristic mutations. Some of these characteristic mutations have shown to generate immunogenic neoepitopes suitable for targeted immunotherapy.
Published first November 15, 2021
Gesehen am 20.01.2022